If
![\frac{ log(a) }{b - c} + = \frac{ log(b) }{c - a} = \frac{ log(c) }{a - b} \frac{ log(a) }{b - c} + = \frac{ log(b) }{c - a} = \frac{ log(c) }{a - b}](https://tex.z-dn.net/?f=+%5Cfrac%7B+log%28a%29+%7D%7Bb+-+c%7D++%2B+%3D++%5Cfrac%7B+log%28b%29+%7D%7Bc+-+a%7D++%3D++%5Cfrac%7B+log%28c%29+%7D%7Ba+-+b%7D+)
Then Find The Value of
![{a}^{a} {b}^{b} {c}^{c} = ? {a}^{a} {b}^{b} {c}^{c} = ?](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7Ba%7D++%7Bb%7D%5E%7Bb%7D++%7Bc%7D%5E%7Bc%7D++%3D++%3F)
#Don'tSpam
Answers
Answered by
14
Answer:
Then Find The Value of
ur answer in this attachment☺
Attachments:
![](https://hi-static.z-dn.net/files/d11/ac9192874c5da1e6bc6cfce51fab340e.jpg)
Answered by
232
✧If ![\dfrac{ log(a) }{b - c} = \dfrac{ log(b) }{c - a} = \dfrac{ log(c) }{a - b} \dfrac{ log(a) }{b - c} = \dfrac{ log(b) }{c - a} = \dfrac{ log(c) }{a - b}](https://tex.z-dn.net/?f=+%5Cdfrac%7B+log%28a%29+%7D%7Bb+-+c%7D++%3D+%5Cdfrac%7B+log%28b%29+%7D%7Bc+-+a%7D+%3D+%5Cdfrac%7B+log%28c%29+%7D%7Ba+-+b%7D+)
Then Find The Value of
GIVEN:-
TO FIND:-
SOLUTION:-
☞Let
(Multiplying a on both side)
☞As we know,
So,From Above:
______(i)
☞Similarly,
______(ii)
☞And also,
______(iii)
☞Adding Equation (i),(ii),(iii)
(since, )
☞So
Since,
Therefore,
ADDITIONAL INFORMATION
Some Important Trigonometric Formulas:-
✯
✯loga+logb=logab
✯loga-logb=log(a/b)
✯
✯
✯
✯
Similar questions